Business Turnaround: Looking From a Diagnostic View - Panicker, Sunita (Ushus Journal of Business Management, 2004)
A business turnaround appears on the surface to be a difficult task for any manager. The reasons for the company downturn are always not clear. You never know for sure if a poor decision, a poor leadership team or general industry downturn is to blame. Nevertheless, what is clear is the firm needs a business turnaround... and fast! A turnaround situation demands immediate attention to problems, arising from the client’s customers, creditors, employees or competitors. The utmost confidentiality must be maintained to protect the market image of the company through out this time. Restructuring is for the best of times as it is for the worst of times. Most managers think of restructuring only when it is the worst of times. This compels them to restructure leaving not much leverage for options. Restructuring is best achieved when the enterprise is healthy and robust. Restructuring is relevant to all organization, failing and faltering as it is to healthy, robust and growing. Restructuring is as relevant intervention for public enterprises, as it is for private ones. In the past before the the economic reforms both public and private enterprises were relatively inflexible. Today, restructuring is more rampant in the private sector, than in the public sector. Both need it urgently and continuously. The business environment metamorphosed by globalisation. IT and Telecom has made restructuring necessary for survival. Sickness had wider ramifications. One must look at the problem from a diagnostic angle. There are various stages of turnaround, which is prescribed by Turnaround Management Association for successful turnarounds. The turnaround strategies adopted by various companies will give us insight into the success of a company.